Thermal neutron transmutation doping of GaN semiconductors - R. Barber (Nature Portfolio, 2020)
Abstract High quality Ge doping of GaN is demonstrated using primarily thermal neutrons for the first time. In this study, GaN was doped with Ge to concentrations from 1016 Ge atoms/cm3 to 1018 Ge atoms/cm3. The doping concentrations were measured using gamma-ray spectroscopy and confirmed using SIMS analysis. The data from SIMS analysis also show consistent Ge doping concentration throughout the depth of the GaN wafers. After irradiation, the GaN was annealed in a nitrogen environment at 950 °C for 30 min. The neutron doping process turns out to produce spatially uniform doping throughout the whole volume of the GaN substrate.